2022
DOI: 10.1002/cae.22487
|View full text |Cite
|
Sign up to set email alerts
|

Flipped classroom model applications in computing courses: Peer‐assisted groups, collaborative group and individual learning

Abstract: The Flipped Classroom (FC) provides various opportunities to ensure active learning in a student‐based learning environment. In the literature, it is pointed out that the FC model provided a positive contribution to the teaching process when it was used for learning environments in past studies. Besides this, it is seen that FC was integrated into a learning method and the results were generally associated with only FC. From this point of view, it is thought that the methodological effect of FC needs to be exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Meanwhile, Wu et al (2023), through a controlled experiment, found that peer feedback can effectively enhance the English academic writing proficiency of Chinese doctors. Similarly, Durak (2022) employed a controlled experimental approach and implemented four different blended teaching methods in classrooms. The research findings indicate that students using peer-assisted methods are more likely to achieve success compared to those using other methods.…”
Section: Socio-educational Environmentmentioning
confidence: 99%
“…Meanwhile, Wu et al (2023), through a controlled experiment, found that peer feedback can effectively enhance the English academic writing proficiency of Chinese doctors. Similarly, Durak (2022) employed a controlled experimental approach and implemented four different blended teaching methods in classrooms. The research findings indicate that students using peer-assisted methods are more likely to achieve success compared to those using other methods.…”
Section: Socio-educational Environmentmentioning
confidence: 99%
“…Most of these studies have demonstrated that FC has multiple effects on students, such as selfregulation [59], self-efficacy [9,60], self-directed learning [11], and deep learning [61].…”
Section: The Effectiveness Of Flipped Classroommentioning
confidence: 99%
“…In the field of FC, practitioners have mainly reduced students' cognitive load while taking CS courses by combining other teaching strategies with FC, such as the use of scaffolding [64], concept mapping [65], and TL (team learning) interventions [66]. Anxiety is another challenge in implementing FC in the field of CS education, mainly computer anxiety and social anxiety, and studies have shown that adequate online learning preparation before class and peer support groups can reduce computer anxiety faced by students during the application of the FC model and improve academic performance [60]. Meanwhile, students must demonstrate a greater sense of responsibility to control and monitor their own learning in order to make pre-course online learning more meaningful [67].…”
Section: The Challenges Of Flipped Classroommentioning
confidence: 99%
“…a) The theory of social constructivism holds that knowledge is formed through social interaction. Students' collaborative learning in groups can promote students' communication and cooperation, so as to enable students to jointly build knowledge and promote the cultivation of students' social skills [17].…”
Section: Collaborative Learning Strategiesmentioning
confidence: 99%